Exploring the research gaps in climate security for Somalia - Carneiro, Bia; Sax, Niklas; Pacillo, Grazia (2023)
In a multi-method approach the working paper explores potential research gaps within climate security pathways in Somalia. Through an iterative process a qualitative analysis of existing pathways leading from climate-related risks to forms of insecurity and conflict, has been complemented vis a vis a network analysis of exisiting academic literature on Web of Science, to explore outlooks for future research on climate security in Somalia. The analysis identified five preliminary pathways and their potential research gaps: Resource Access and Availability; Livelihood and Food Insecurity; Disaster and Conflict Displacement; Armed Groups Tactics and Exploration; Social Vulnerability and Fragility. In the proposed next steps, the research will qualitatively assess the identified links within the pathways, validate findings in an expert consultation and establish a confidence scaling of the research available.